Wasiyyah (Islamic will) adoption and the barriers in Islamic inheritance distribution among Malaysian Muslims - Ghul, Z. H.; Yahya, Mohamed Hisham; Abdullah, Amalina (A R C Publications, 2015)
The amount of frozen assets due to unclaimed inheritance in the Muslim society in Malaysia is significant. There are is about a million land titles that are still in the name of the deceased owners. In 2012, the amount of frozen estates is estimated to be around RM45 billion and this figure is expected to increase further. This statistics is alarming and calls for an urgent need in solving the problem of unclaimed inheritance in the Muslim society in Malaysia. It is imperative to teach that Muslims have a clear idea on the appropriate instruments and course of actions in estate planning. The majority of muslims in Malaysia do not view estate planning as a serious matter. Previous researches attest that some of the Muslims, themselves, are sceptical about making a Wasiyyah (Islamic Will). This is the evidencenced substantiated by the large number of Malaysian Muslims who do not have Wasiyyah. In general, the level of awareness of Wasiyyah practice is not very encouraging, specifically, among Malaysian Muslims. The findings from this study show that 1) knowledge on the concepts of Islamic estate planning and 2) awareness of the importance wealth management have a significant effect towards Wasiyyah practices. In terms of barriers in Islamic inheritance distribution, the biggest obstacles among all the factors are lengthy estate management and distribution process.